Transitioning from paediatric to HIV adult care services for adolescents and young people living with HIV in the African region: a scoping review protocol - Noeline Nakasujja; Andrew Sentoogo Ssemata; Eugene Kinyanda (BMJ Open)
Introduction The number of children living with HIV is increasing worldwide and is a major public health concern as they grow into adolescence and young adulthood with increasing access to antiretroviral therapy (ART) especially in the African region. There is a pressing need to transfer them from paediatric to adult care which has implications for their well-being. The objective of this scoping review is to systematically review published and unpublished literature to understand the extent and type of evidence in relation to the transition of adolescents to adult HIV clinics in the African region.Methods and analysis Following the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses—Extension for Scoping Review) guidelines for conducting a scoping review, we will systematically search online bibliographic databases including PubMed, EMBASE, Google Scholar and bibliographies of pertinent articles. This will be supplemented by searches in grey literature databases. Two reviewers will independently review all articles to determine if they meet eligibility criteria. Any conflicts will be resolved after discussion with a third reviewer to ensure accurate and reliable data collection. Both quantitative and qualitative results will be extracted from all included articles and synthesised in a narrative form in response to the review questions.Ethics and dissemination The scoping review does not require ethics approval as we will collect and review existing literature and materials. The results will be disseminated through a peer-reviewed publication, conference presentations and stakeholder meetings to support clinicians, health experts and policy makers develop guidelines and evidence-based transition protocols favourable for the populations in the African region to minimise challenges associated with the transition process.